Seed quality of winter wheat varieties after black fallow depending on organo-mineral fertilizer application in the Left-Bank Forest-Steppe zone of Ukraine - С. В. Авраменко (Plant Varieties Studying and Protection)
Purpose. To determine the effect of the basic organo-mineral fertilizer on the formation and stability of grain quality of winter wheat varieties in multiple crop rotation after black fallow as a predecessor.